MONITORING OF PERSISTENT ORGANIC POLLUTANTS IN THE SOIL OF THE CHECHEN REPUBLIC - I. Ya. Shakhtimirov; S. Kh. Isaeva; Kh. N. Askhabova; K. A-V. Shuipov (Юг России: экология, развитие, 2014)
The content of persistent organic pollutants in agricultural and residential areas of the Czech Republic. Elevated levels of PCBs in samples of agricultural use found near the city of Grozny and Argun. Dioxin is the most polluted soil in areas of the asphalt plants.Mesker-Yurt. The main sources that supply dioxins into the environment from manufacturing facilities in Grozny, Argun, Gudermes, Shali. Monitoring of the environmental situation in the Czech Republic is needed to develop and implement a national program for the protection of the environment and the population of persistent organic pollutants.